Uma Renda Básica resolve o problema da pobreza? Amartya Sen, Philippe Van Parijs e a carestia contemporânea - Santos, Cliciele Rosa (2021)
Poverty is a multidimensional problem and therefore any work that intends to discuss its effects cannot refrain from seeking a more comprehensive understanding of its various aspects. The first part of this work seeks to understand how a low income can result in different subjective problems, from the lack of autonomy to the pejorative way in which the poor individual is seen by the rest of society and, therefore, their additional difficulty in raising their self-esteem. This brings us closer to the definition of poverty proposed by the Indian philosopher and economist Amartya Sen, a definition that goes beyond the economic aspect and considers poverty as a lack of individual freedom, as an absence of capabilities. However, Sen understands the importance of a material basis in this process of increasing individual autonomy. For him, public policies to fight poverty must not only satisfy the most basic needs of those served, but also enable beneficiaries to develop new capacities. However, receiving a focused benefit results in the stigmatization of those served by such programs. From this, it is possible to think about how the distribution of income in a universal and unconditional way would eliminate the stigmatization that befalls those who depend on social assistance, as such stigmatization would not exist if income were guaranteed as a universal right. Thus, the second part of our research exposes the Basic Income proposal by Philippe Van Parijs, which advocates that a basic income be distributed unconditionally to achieve a fairer and freer society. That said, the final part of the research will seek to discuss to what extent the Basic Income defended by Van Parijs contributes to the elimination of poverty in a broader sense, as proposed by Sen. We will try to demonstrate that, as it seems to us, as important as it is in the fight against poverty, a basic income alone is insufficient for the complete eradication of this problem. The proposal of a universal basic income is only effective in combating poverty when combined with the guarantee of basic services offered by the State.